Does the Exchange Rate Regime Affect Macroeconomic Performance : Evidence from Transition Economics - Domac, Ilker; Peters, Kyle; Yuzefovich, Yevgeny (World Bank, Washington, DC, 2014)
To examine whether a country's exchange rate regime has any impact on inflation and growth performance in transition economies, the authors develop an empirical framework that addresses some of the main problems plaguing empirical work in this strand of the literature: the Lucas critique, the endogeneity of the exchange rate regime, and the sample selection problem. Empirical results demonstrate that the exchange rate regime does affect inflation performance. the results suggest that: 1) Transition countries with intermediate arrangements might reduce inflation if they were to adopt a fixed regime. 2) Switching from a floating regime to an intermediate regime might not reduce inflation. 3) An unanticipated float--when a country whose fundamentals make it unlikely to adopt another regime adopts a floating regime--results in lower inflation. Based on their results, it is not possible to infer more about one particular exchange rate regime being superior to another in terms of growth performance. But empirical findings do underscore the different effects that policy variables--and other variables influencing economic activity--have on growth under different exchange-rate arrangements.